2019
DOI: 10.1016/j.ijcard.2018.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fat mass and fat-free-mass are associated with incident hypertension in four population-based studies from Germany

Abstract: Our data suggests that the well-established association between obesity and blood pressure levels might be more related to body composition rather than to total body weight per se. Our findings indicate that gaining or losing FFM has substantial impact on the development or reversion of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…BMI is an independent risk factor for hypertension in both men and women, and high fat mass is associated with a higher risk of hypertension, even in non-obese populations [ 34 ]. In contrast, it has also been shown that a reduction in fat-free mass is more strongly associated with the normalization of blood pressure than a reduction in fat mass [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMI is an independent risk factor for hypertension in both men and women, and high fat mass is associated with a higher risk of hypertension, even in non-obese populations [ 34 ]. In contrast, it has also been shown that a reduction in fat-free mass is more strongly associated with the normalization of blood pressure than a reduction in fat mass [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in body composition characteristics and intrarenal dopamine are associated with hypertension [30,31]. Moreover, FFM, the more metabolically active body portion, has been reported to have a more predominant effect on the human brain [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study has shown that a higher body fat percentage (BF%) is associated with an increased risk of hypertension, even in non-obese individuals (8). Furthermore, an increase in fat mass (FM) and fat-free mass (FFM) is associated with incident hypertension (9). These findings suggest that not only BMI but also differences in body composition are associated with hypertension.…”
Section: Introductionmentioning
confidence: 99%